Occupational Stress and Job Satisfaction among the Non-Academic Staff: A Study Based on the University of Jaffna - Queenciya, K.; Rajkumar, A. (Faculty of Arts University of Jaffna, Sri Lanka, 2025)
The present study explores the levels of occupational stress and job satisfaction among the non-academic staff at the University of Jaffna. The primary aim is to assess how these two factors are experienced and whether they are interrelated. This research follows a quantitative data, with a study population of 100 non-academic staff selected through a random sampling method. Primary data were collected using standardized Occupational Stress and Job Satisfaction Scales, while secondary data were obtained from books, journal articles, and internet sources. Data analysis was conducted using statistical package for social sciences (SPSS - version 27), applying regression analysis, correlation analysis, one-sample t-test, independent samples t-test, and ANOVA. Findings reveal that the non-academic staff experience a moderate level of occupational stress (x̄ = 21.36, p = 0.000) and an average level of job satisfaction (x̄ = 35.10, p = 0.000). No significant relationship was found between occupational stress and job satisfaction (R = -0.109, p = 0.279). However, designation significantly affects occupational stress (F = 3.755, p = 0.007). Additionally, job satisfaction is influenced by salary (R² = 0.033, F = 4.379, p = 0.039), work faculty (R² = 0.040, F = 5.083, p = 0.026), and age (R² = 0.039, F = 5.013, p = 0.027). A significant gender difference in job satisfaction was also identified, with males reporting higher satisfaction levels (x̄ = 36.73) than females (x̄ = 33.53; F = 8.805, p = 0.004). The study suggests that while the overall levels of occupational stress are moderate, and job satisfaction is average, there are significant variations based on demographic factors such as designation, salary, and gender. These variations indicate the need for targeted interventions that can address the specific concerns of different groups within the non-academic staff. In conclusion, non-academic staff at the University of Jaffna experience moderate occupational stress and average job satisfaction. It is recommended that the university can establish a well-structured employee wellness and recognition program to reduce stress and enhance job satisfaction, particularly addressing salary concerns and fostering a supportive work environment.
Keywords: Job satisfaction; Non – academic staff; Occupational stress; University of Jaffna